Current developments and challenges for the British Journal of Psychology. - Schweinberger, Stefan R.; Franz, Volker H.; Palermo, Romina (British Journal of Psychology, 2018)
The article focuses on developments related to the British Journal of Psychology. It highlights current data for submission activities and publications in the more recent period between 2013 and 2016. It refers to target articles on psychological models of aesthetic perception published by the journal in recent years.